Analisis Balik Kestabilan Lereng Pada Pit Eagle 1 PT. Bumi Karya Makmur Jobsite PT. IPC Bantuas, Samarinda, Kalimantan Timur - deki Irawan; Yoszi Mingsi Anaperta (Departemen Teknik Pertambangan FT UNP, 2022)
PT. Bumi Karya Makmur is one of the companies engaged in coal mining contractors. PT. Bumi Karya Makmur is a mining contractor trusted by PT. International Prima Coal as the holder of IUP OP (Production Operation Mining Business License) to carry out coal mining activities which located in Bantuas, Palaran District, Samarinda City, East Kalimantan Province. Mining activity is carried out using the Open Pit Mining method. In May 2021, a landslide occurred on the western slopes of Pit Eagle 1 which have made disrupted mining activities because the front work was buried by slope of landslide material. The landslide was caused by the actual geometry of the slopes in the field which is too steep around 80° for single slope and there were puddles of water on the slopes that makes the slope in the saturated state. The slope stability analysis of the western area at Pit Eagle 1 used the Probabilistic Monte Carlo method, where the initial soil data were: cohesion (c) = 93,272 kN/m2 and internal shear angle (ϕ) = 20,122˚; sandstone: (c) = 87,886 kN/m2 and (ϕ) = 28,014; mudstone: c = 129.983 kN/m2 and = 31,317˚. Analysis the value of the factor of safety (FK), the probability of landslides (PK), and slope geometry recommendation using the Bishop Simplified method. The results of this research are, firstly, the slope safety factor value at Pit Eagle 1 in the saturated state before the landslide is 1.253 with a landslide probability value of 0%, in the semi-saturated state with FK value is 1.602 with a landslide probability value of 0% and the dry state with a FK value of 1.802 with a probability of avalanche 0%. Secondly, back analysis on the Pit Eagle 1 landslide area resulted in the value of the geotechnical parameter Soil (C) = 88.6 kN/m2 (ϕ) = 20,122o; Sandstone: (c) = 87,886 kN/m2 and (ϕ) = 28,014o; Mudstone (C) = 69.65 kN/m2 (ϕ) = 23.316o. Third, the geometry recommendation of slope at Pit Eagle 1 with an overall slope height of 40 meters, that namely with an overall slope angle of 52˚ with a single slope height of 8 meters, a bench width of 5 meters, and a single slope angle for Soil and Sandstone materials, while for a single slope angle for Mudstone materials is 70°.